Modelagem hidrológica para previsão de vazões de pico na Bacia do Rio Embu Mirim utilizando o método de I-PAI-WU - Oliveira, Layssa de Moura (Universidade Federal de São Carlos, 2024)
In the scenario of climate transformations, water resources play a vital role, emphasizing the urgent need to preserve, manage, and adapt humanity's water sources to ensure sustainability and well-being for future generations. Within this context, hydrological modeling is essential to understand flow patterns and risks associated with extreme events such as floods. Accordingly, this study focuses on hydrological modeling in the Embu Mirim River Basin, located in the state of São Paulo (UGRHI-06), with a focus on predicting critical precipitation intensities and, consequently, peak flows. Using the I-PAI-WU method, an enhancement of the rational method for basins between 2 and 200 km², the research aims to analyze and predict maximum water flows in the region. The methodological process included basin delineation using geoprocessing tools, adopting the calculation algorithm specified for the chosen hydrological model, and utilizing rainfall equations from various sources for municipalities within the basin. Although the results indicated a very small variation in precipitation intensity values for Itapecerica da Serra (an increase of 2%), a significant increase (28%) in critical rainfall values was observed for Embu das Artes, demonstrating a noteworthy alteration in the rainfall pattern for this locality. Consequently, the peak flow results followed the same trend. It is noteworthy that, in this modeling, a hypothetical scenario was considered, disregarding the presence of downstream flowregulating structures such as dams. Finally, the I-PAI-WU method proved to be of simple application, requiring basic data such as precipitation intensity, drainage area, runoff coefficient, and spatial distribution factor of rainfall, making it suitable for small and mediumsized basins and short-duration rainfall events.
Hydrological modeling for peak flow prediction in the Embu Mirim River Basin using the I-PAI-WU method
Modelado hidrológico para predicción de caudales máximos en la Cuenca del Río Embu Mirim utilizando el método I-PAI-WU
Keywords: Modelagem hidrológica; Bacia do Embu Mirim; Intensidade de precipitação; I-PAI-WU; Embu Mirim Basin; Hydrological modeling; Precipitation intensity; I-PAI-WU; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS